Impact of the War in Ukraine on Farm Profitability and the Attractiveness of Environmental Measures in Germany - Raphaela Ellßel; Friedrich Wus̈temann; Frank Offermann; Thomas de Witte (German Journal of Agricultural Economics (GJAE), 2022)
The war in Ukraine has led to massive price increases for agricultural inputs and products. This paper examines the effects on farm profitability and the consequences for the adoption of eco-schemes on arable farms. We use the large farm sample of the German Farm Accounting Data Network (FADN) to identify the average income effects and to highlight the heterogeneity of the effects and their drivers. Building on these results, we analyse farms' adaptation strategies with a focus on changes in nitrogen input intensity and participation in environmental measures ("eco-schemes") of the new Common Agriculture Policy (CAP). Our results suggest that income effects are heterogeneous and subject to considerable uncertainty about the near future, and that many farms are likely to benefit from the short-term price effects of the war in Ukraine. Against this background, the efficiency of financial assistance under the EU crisis reserve would have benefited from a stronger focus on liquidity loans and ex-post hardship support. Our analysis also shows strong implications for participation in eco-schemes. The results cast significant doubts on the effectiveness and efficiency of the eco-schemes introduced by the new CAP, beyond the observed impact of the war in Ukraine.
Keywords: 330; Ukraine war; income; eco-schemes; CAP; nitrogenfertilisation